2003
DOI: 10.1007/s00441-003-0762-9
|View full text |Cite
|
Sign up to set email alerts
|

STRO-1, HOP-26 (CD63), CD49a and SB-10 (CD166) as markers of primitive human marrow stromal cells and their more differentiated progeny: a comparative investigation in vitro

Abstract: There is widespread interest in the use of bone marrow stromal cells (BMSC) for tissue reconstruction and repair and for gene therapy. BMSC represent the differentiated progeny of CFU-F, which however comprise a developmentally heterogeneous population as is reflected in the cellular heterogeneity of the cell populations to which they give rise. We have compared the efficacy of monoclonal antibodies recognising a series of stromal antigens, viz. STRO-1, HOP-26, CD49a and SB-10/CD166, as tools for the enrichmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
92
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(105 citation statements)
references
References 53 publications
9
92
1
3
Order By: Relevance
“…Stro1 was used as a marker of undifferentiated stem cells in preference to other markers as it recognises nonhaematopoietic progenitor cell with a stable undifferentiated phenotype [35]. Also, we previously found that expression of other markers is inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Stro1 was used as a marker of undifferentiated stem cells in preference to other markers as it recognises nonhaematopoietic progenitor cell with a stable undifferentiated phenotype [35]. Also, we previously found that expression of other markers is inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, we found that CD18 is highly expressed on the BMSSCs of the early passages after their purification from bone marrow. Given such a distinct pattern of expression, CD18 could be a useful surface marker for cell sorting to enrich the stromal stem cell population, because most of the other surface markers for stromal stem cells, including STRO-1, CD106͞VCAM-1, CD146͞MUC-18, HOP-26, CD49A͞integrin ␤ 1 , and SB-10͞ CD166 (20,22,28), are expressed both on progenitor and on differentiated mesenchymal cells. As proof of principle, we isolated BMSSCs from human bone marrow aspirates by cell sorting using both CD18 and STRO-1, a cell marker commonly used for stromal stem cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…As marrow is a complex mixture of cells a more defined starting cell population subset can be isolated from the mixture on the basis of epitope expression such as Endoglin (Haynesworth et al 1992;Majumdar et al 2000) and STRO-1 (Simmons & Torok-Storb, 1991;Howard et al 2002;Stewart et al 2003) antibody selection procedures. These cells can be removed from marrow and used to enhance materials such as the filler used for stabilizing artificial hip joints or for joining critical sized defects in bone that would not otherwise heal (Tilley et al 2006).…”
Section: Bone Marrow-derived Mesenchymal Stem Cellsmentioning
confidence: 99%